Bystander hyperactivation of preimmune CD8+ T cells in chronic HCV patients - Cécile Alanio; Francesco Nicoli; Philippe Sultanik; Tobias Flecken; Brieuc Perot; Darragh Duffy; Elisabetta Bianchi; Annick Lim; Emmanuel Clave; Marit M van Buuren; Aurélie Schnuriger; Kerstin Johnsson; et al. (eLife, 2015)
Chronic infection perturbs immune homeostasis. While prior studies have reported dysregulation of effector and memory cells, little is known about the effects on naïve T cell populations. We performed a cross-sectional study of chronic hepatitis C (cHCV) patients using tetramer-associated magnetic enrichment to study antigen-specific inexperienced CD8+ T cells (i.e., tumor or unrelated virus-specific populations in tumor-free and sero-negative individuals). cHCV showed normal precursor frequencies, but increased proportions of memory-phenotype inexperienced cells, as compared to healthy donors or cured HCV patients. These observations could be explained by low surface expression of CD5, a negative regulator of TCR signaling. Accordingly, we demonstrated TCR hyperactivation and generation of potent CD8+ T cell responses from the altered T cell repertoire of cHCV patients. In sum, we provide the first evidence that naïve CD8+ T cells are dysregulated during cHCV infection, and establish a new mechanism of immune perturbation secondary to chronic infection.